MORPHOMETRIC ANALYSIS OF SUBMUCOSAL AND MYENTERIC NERVE PLEXUSES IN CHRONIC INFLAMMATORY BOWEL DISEASE IN CHILDREN - Mehmedović, Amin; Kotur , Milica (Medicinski podmladak, 2025)
ABSTRACTIntroduction: Chronic inflammatory bowel diseases (IBD) include ulcerative colitis (UC) and Crohn's disease (CD), characterized by relapses and an insufficiently clarified etiology. The enteric nervous system (ENS) consists of neuronal cells distributed along the gastrointestinal tract, organized into the submucosal Meissner's and myenteric Auerbach's plexuses. The glial cell index (GCI) represents the ratio of the number of glial cells to ganglion cells within the ganglia of the ENS.Aim: The aim of this study is a morphometric analysis of the ENS in intestinal samples from surgically treated pediatric patients with CD and UC.Material and methods: Histological slides from the archives of the Institute of Pathology, Faculty of Medicine, University of Belgrade, were analyzed. The study included an analysis of intestinal wall sections from pediatric patients with IBD (experimental group) and those with uncomplicated familial adenomatous polyposis syndrome (control group). Using the ImageJ software, five microphotographs of submucosal and myenteric nerve plexuses stained with Masson trichrome and captured with an Olympus DP70 digital camera at x400 magnification were analyzed.Results: A significant difference in the GCI value in the myenteric plexus of the colon was observed between the experimental and control groups. No significant difference in the GCI value in the submucosal plexus of the colon was found between the two groups. A minimal difference in the GCI value within the experimental group was observed in the submucosal plexus sections.Conclusion: This study presents a unique analysis of glial cells in CD, UC, and the control group in the submucosal and myenteric plexuses. The results indicate a disruption of GCI in the ENS in IBD, which likely represents the morphological substrate for intestinal motility disorders in these conditions.
Keywords: Crohn’s disease, ulcerative colitis, morphometry, enteric nervous system